Strategy Analysis of Thai Rice Development and Processing and Competition in World Trade Market - Jongmeesuk, Thanapat; Tossamas, Pattarapon; worapreda, Paiwan (Journal for Developing the Social and Community, 2017)
Rice is important plant world people’s consumption, the important production source, mostly is in Asian which includes Thailand especially the stem exporters of the world, rice is the one making income and economy of country, and it is main food for Thai people. Therefore, the rice has been developed from past until presently in order to be able compete to other countries. However, Thai rice has encounter problems in regard to export from export competition such as the competition from low cost countries lead to Thailand has to reform the export strategy such a Processing both food and products from rice, these is to make Thai rice more attractive helping farmers and Thai economy going om continually.